Comorbidities and ethnic health disparities in the UK biobank. Issue 3 (11th July 2022) - Teagle, Whitney L; Norris, Emily T; Rishishwar, Lavanya; Nagar, Shashwat Deepali; Jordan, I King; Mariño-Ramírez, Leonardo
Abstract: Objective: The goal of this study was to investigate the relationship between comorbidities and ethnic health disparities in a diverse, cosmopolitan population. Materials and Methods: We used the UK Biobank (UKB), a large progressive cohort study of the UK population. Study participants self-identified with 1 of 5 ethnic groups and participant comorbidities were characterized using the 31 disease categories captured by the Elixhauser Comorbidity Index. Ethnic disparities in comorbidities were quantified as the extent to which disease prevalence within categories varies across ethnic groups and the extent to which pairs of comorbidities co-occur within ethnic groups. Disease-risk factor comorbidity pairs were identified where one comorbidity is known to be a risk factor for a co-occurring comorbidity. Results: The Asian ethnic group shows the greatest average number of comorbidities, followed by the Black and then White groups. The Chinese group shows the lowest average number of comorbidities. Comorbidity prevalence varies significantly among the ethnic groups for almost all disease categories, with diabetes and hypertension showing the largest differences across groups. Diabetes and hypertension both show ethnic-specific comorbidities that may contribute to the observed disease prevalence disparities. Discussion: These results underscore the extent to which comorbidities vary among ethnic groups and reveal group-specific disease comorbidities that may underlie ethnic health disparities. Conclusion: The study of comorbidity distributions across ethnic groups can be used to inform targeted group-specific interventions to reduce ethnic health disparities. Lay Summary: Despite overall improvements in public health, ethnic health disparities persist. Ethnic minority groups living in cosmopolitan societies continue to bear a disproportionate burden of morbidity and mortality. Ethnic health disparities are characterized by complex patterns of comorbidities, that is, the presence of more than one disease at the same time in an individual patient. The aim of this study was to investigate the relationship between comorbidities and ethnic health disparities in the United Kingdom. Our study relied on the UK Biobank, a progressive cohort of more than half a million participants. We measured differences in disease prevalence and patterns of comorbidities across 5 UK ethnic groups: Asian, Black, Chinese, Mixed, and White. Study participants who identified as Asian showed the highest disease prevalence and largest number of comorbidities, followed by participants from the Black and then White ethnic groups; Chinese participants have the lowest overall disease prevalence and comorbidities. Patterns of comorbidities vary widely among ethnic groups in the United Kingdom, and there are a number of group-specific disease comorbidities that contribute to ethnic health disparities, for example, for diabetes and hypertension. We hope that our results on comorbidities can be used to inform targeted group-specific interventions in support of health equity.